2020
DOI: 10.1038/s41375-020-0868-z
|View full text |Cite
|
Sign up to set email alerts
|

Isatuximab plus pomalidomide and dexamethasone in relapsed/refractory multiple myeloma patients with renal impairment: ICARIA-MM subgroup analysis

Abstract: The randomized, phase 3 ICARIA-MM study investigated isatuximab (Isa) with pomalidomide and dexamethasone (Pd) versus Pd in patients with relapsed/refractory multiple myeloma and ≥2 prior lines. This prespecified subgroup analysis examined efficacy in patients with renal impairment (RI; estimated glomerular filtration rate <60 mL/min/1.73 m²). Isa 10 mg/kg was given intravenously once weekly in cycle 1, and every 2 weeks in subsequent 28-day cycles. Patients received standard doses of Pd. Median progression-fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
58
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 31 publications
2
58
0
9
Order By: Relevance
“…In this study, MM patients with renal impairment were more likely to be older and to present with ISS stage III at diagnosis, which has been reported in a previous phase III study 11 . Patients with renal impairment exhibited decreased OS compared with non-renally impaired patients.…”
supporting
confidence: 77%
“…In this study, MM patients with renal impairment were more likely to be older and to present with ISS stage III at diagnosis, which has been reported in a previous phase III study 11 . Patients with renal impairment exhibited decreased OS compared with non-renally impaired patients.…”
supporting
confidence: 77%
“…The median PFS was 11.5 months in the Isa-Pd arm vs. 6.5 months in Pd arm (HR, 0.596, p = 0.001) [37]. Subgroup analysis of this trial showed significant improvement of PFS in patients with renal impairment (<60 mL/min/1.73 m 2 ), PFS was 9.5 months in Isa-Pd arm and 3.7 months in Pd arm (HR 0.50, p not reported) [38]. The effect was also maintained in elderly population including patients >75 years [39].…”
Section: Combination Treatment Of Anti Cd38 and Imid In Rrmmmentioning
confidence: 70%
“…Добавление изатуксимаба к схеме терапии не сопровождалось увеличением частоты отмены терапии и изменениями в качестве жизни (по опроснику QLQ-30) [16]; а в обеих прогностически неблагоприятных подгруппах пациентов с РРММ (тяжело предлеченных -более 3 линий предшествующей терапии и у пациентов с ПН) качество жизни, связанное с состоянием здоровья, лучше поддерживалось на триплете I-Pd по сравнению с дуплетом Pd [19].…”
Section: изатуксимабunclassified
“…Отдельного внимания заслуживает анализ данных не только эффективности, но и безопасности комбинации I-Pd у пациентов с ПН, так как нарушения функций почек часто встречаются в популяции пациентов с ММ и связаны как с самим заболеванием, так и с назначаемой терапией. Согласно данным подгруппового анализа в исследовании ICARIA-MM [16] у пациентов с ПН медиана полученных циклов терапии не отличалась от таковой у пациентов без ПН и составила соответственно 10 циклов (1-18) против 10 циклов (1-19) [16]. Частота НЯ, впервые возникших или ухудшившихся после начала исследуемой терапии ≥3-й степени тяжести, была сравнимой у пациентов с ПН и без нее (90,7% против 86%) в группе пациентов, получавших I-Pd.…”
Section: изатуксимабunclassified